Implementation of an efficient web-based movie ticket purchasing system in the context of Bangladesh - Gazi Zahirul Islam; Isrut Jahan Zinnia; Md. Fokhray Hossain; Md. Riazur Rahman; Aman Ullah Juman; Al Nahian Bin Emran (Institute of Advanced Engineering and Science, 2020)
The ‘Movie Ticket Purchase System’ is a web-based application. In this application, people can purchase movie tickets from all movie theatres in Bangladesh. Before purchasing a ticket, people have to do registration or login. This website builds by PHP and JavaScript for back-end; HTML, CSS for front-end. All steps of the software development life cycle are addressed properly to develop and implement the software. This website has three panels: one for the Admin, one for the Theatre Assistant and another for the Customer/User. Admin can insert the theatres, and Theatre Assistant handled maximum manual works on the website like movie add, delete, stop running, screen adds, etc. This is the first website in Bangladesh where people can purchase tickets from multiple movie halls and the site is only dedicated to this purpose. The website is very user-friendly and attractive that can give comfort to the end users. Also, the theater owners that have no digital platform for selling tickets can be a member of our service and get the opportunity of using digital platform.